Discovering an Orphan Source of Ionizing Radiation with Respect to Occupational Safety and Health - Miroslav Tomek; Jan Strohmandl; Pavel Tomášek; Dušan Vičar (Salehan Institute of Higher Education, 2022)
Compliance with the principles of occupational safety and health is one of the preconditions for avoiding emergency events. Without a doubt, this is one of the underlying duties of every employer or operator of waste recycling centers. The risk to health resulting from an orphan source of ionizing radiation in the form of scrap metal is quite high and can affect a significant number of people. As part of the precautions relating to employees, the employer must analyze the risks associated with working with scrap metal and emphasize the possibility of any previous contamination. In practice, various methods and procedures are used to assess the risks at scrap metal collection facilities, which are mostly based on the knowledge and experience of their inspectors. However, this is not usually done by means of appropriate risk analysis methods, which is the main disadvantage. The goal of this article is to point at the risks related to discovering an orphan source of ionizing radiation by using the Ishikawa diagram and the point method. Furthermore, this article also deals with the demarcation of a safety zone with respect to the protection of health and the environment. The specification of risks, the proposal of recommended precautions, and the expeditious demarcation of a safety zone in the case of the intervention of fire brigades in order to protect and/or decontaminate the persons are also included. Doi: 10.28991/CEJ-2022-08-11-013 Full Text: PDF